Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

SMART-assisted discovery of scalaranes from the marine sponge Lendenfeldia sp. and its anti-osteoclastogenesis activity - Quoc-Vu Pham; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Lo-Yun Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai; Tsong-Long Hwang (Phytochemistry, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

New C22-related terpenoid from Formosan marine sponge Lendenfeldia sp. - Quoc-Vu Pham; Hsin-Wei Wang; Yu-Cheng Chen; Yu-Chia Chang; You-Song Cheng; Yun-Shiuan Chen; Mei-Hsien Lee; Jui-Hsin Su; Bo-Rong Peng; Kuei-Hung Lai (Phytochemistry Letters, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Construction of antibacterial-enhanced 2D ZnO@ZIF-8 nanocomposites based on synergistic antimicrobial mechanisms and application in maize long-term storage - Song-Yue Xu; Chao-Shuai Mei; Ke-Yu Zhou; Feng Xiao; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Food Chemistry, 2025)

AIEgen-based porous organic polymer-Ag nanoparticles hybrids with coreaction accelerator amplification and covalent rigidification-enhanced electrochemiluminescence for aflatoxin M1 detection - Jun-Qi Song; Qiu-Yi Peng; Mei-Ling Lu; Shu-Zhen Gao; Wen-Bin Liang; Shaoguang Sun; Ruo Yuan; Dong-Rong Xiao (Food Chemistry, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A novel tin dioxide field effect transistor with PMMAA functionalized organic passivation layer for the detection of the cortisol in saliva - Caiyuan Liao; Rong Zou; Qixin Zhou; Huan-Yu Liu; Song-Mei Liu; Long Fang; Gang Chang; Hanping He (Chemical Engineering Journal, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

Transcription Factor EGR1 Facilitates Neovascularization in Mice with Retinopathy of Prematurity by Regulating the miR-182-5p/EFNA5 Axis - Ningning Peng; Mei Zheng; Bei Song; Rong Jiao; Wenxiang Wang (Biochemical Genetics, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Promoting sensitive colorimetric detection of hydroquinone and Hg2+ via ZIF-8 dispersion enhanced oxidase-mimicking activity of MnO2 nanozyme - Na Liang; Xinyue Ge; Yan Zhao; Lian Xia; Zhi-Ling Song; Rong-Mei Kong; Fengli Qu (Journal of Hazardous Materials, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

SWI2/SNF2 chromatin remodeling ATPases SPLAYED and BRAHMA control embryo development in rice - Qian Xun; Min Mei; Ye Song; Chenyu Rong; Jiajun Liu; Tianhui Zhong; Yanfeng Ding; Chengqiang Ding (Plant Cell Reports, 2022)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phagocytic Removal of Neuronal Debris by Olfactory Ensheathing Cells Enhances Neuronal Survival and Neurite Outgrowth via p38MAPK Activity - Bao-Rong He; Song-Tao Xie; Ming-Mei Wu; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)